The Use of Infographics to Improve Students’ Reading Comprehension Skills - Sudarmaji, Imam; Nurfadilah, Vina; Fauzi, Aziz; Fajrin, Vera (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
Reading comprehension is a difficult thing for students to do. This can happen due to several factors including the learning medium used in the process. The aim of this research was to describe how infographics can improve students’ reading comprehension of procedure texts. This research employed a classroom action research method. The subjects of this study were 33 tenth-grade students. The instruments in this study were tests, questionnaires, observations and interview. The findings of the study showed that students’ reading comprehension improved significantly, as evidenced by the mean score of the post-test being 86 which was higher than the mean score of the pre-test which was 77. In addition, students’ responses to the use of infographics in procedural texts were positive. In this regard, this study suggests that infographic media can be an effective tool to improve reading comprehension skills in various educational settings, which has the potential to benefit EFL learners.